Crime Victims in Indonesia's Criminal Justice System Based on The Criminal Procedure Law (KUHAP) - Santriana Santriana; Desi Anisah; Satria Indra Kesuma (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of this study is to examine how crime victims are treated by Indonesia's criminal justice system. This scientific study was written utilizing the normative legal research method, which employs a statutory approach (act approach). The study's findings demonstrate that Indonesia's criminal justice system, which is based on the Criminal Code (KUHAP), places an undue emphasis on offenders and minimal emphasis on victims. The absence of provisions in the Criminal Procedure Code that address the existence of victims of crime is one indication of this. As a result, the crime victim in this instance serves simply as a witness to establish the defendant's guilt in a court of law. In actuality, victims of crimes as much as criminals face the issue of justice and respect for human rights.